2024
DOI: 10.1111/ppl.14150
|View full text |Cite
|
Sign up to set email alerts
|

A metabolomics perspective on root‐derived plant immunity and phytohormone interaction

Pratibha Demiwal,
Sumedh Tayade,
Shri Ram Yadav
et al.

Abstract: A plant's root system is essential to its survival as it supports anchorage and absorbs water and minerals from the ground. Several microorganisms interact with roots in the rhizosphere, and they can be neutral, positive, or negative. Identifying beneficial and pathogenic microorganisms and limiting or promoting their colonization is essential for roots to survive. Signaling molecules and metabolites play an important regulatory role in determining root‐microbe associations. Phytohormones modulate plant‐microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Untargeted metabolomics has identified lipid indicators of Plasmopara viticola inoculation in grapevines, whereas a study of maize genotypes interacting with nitrogen-fixing PGPB species revealed alterations in plant metabolites owing to bacterial nitrogen fixation (Diwan et al, 2022 ). Despite being underutilized in root-pathogen interaction studies compared to other omics methods, untargeted metabolomics provides valuable insights into plant-microbial interactions across various tissues, aiding the development of more effective crop and plant protection strategies (Demiwal et al, 2024 ). Detailed metabolomic analysis revealed Pseudomonas syringae -triggered hyperaccumulation of dihydrocamalexic acid (DHCA) in the apoplastic space of pad3 but not in cyp71a12/a13 plants, and infiltration of DHCA into cyp71a12/a13 mutant leaves restored resistance, indicating its role in restricting P. syringae growth in plants (Singh et al, 2023 ).…”
Section: Omics Approaches Mechanism In Beneficial Plant-microbe Inter...mentioning
confidence: 99%
“…Untargeted metabolomics has identified lipid indicators of Plasmopara viticola inoculation in grapevines, whereas a study of maize genotypes interacting with nitrogen-fixing PGPB species revealed alterations in plant metabolites owing to bacterial nitrogen fixation (Diwan et al, 2022 ). Despite being underutilized in root-pathogen interaction studies compared to other omics methods, untargeted metabolomics provides valuable insights into plant-microbial interactions across various tissues, aiding the development of more effective crop and plant protection strategies (Demiwal et al, 2024 ). Detailed metabolomic analysis revealed Pseudomonas syringae -triggered hyperaccumulation of dihydrocamalexic acid (DHCA) in the apoplastic space of pad3 but not in cyp71a12/a13 plants, and infiltration of DHCA into cyp71a12/a13 mutant leaves restored resistance, indicating its role in restricting P. syringae growth in plants (Singh et al, 2023 ).…”
Section: Omics Approaches Mechanism In Beneficial Plant-microbe Inter...mentioning
confidence: 99%